1998
DOI: 10.1089/jir.1998.18.705
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Hepatic Inflammatory Changes, Circulating Levels of Cytokines, and Response to IFN-α in Chronic Hepatitis C

Abstract: To investigate the relationship among circulating cytokines, inflammation in the liver, and kind of response to interferon-alpha (IFN-alpha) in hepatitis C, we studied 63 consecutive patients (38 male, 25 female), treated with IFN for up to 1 year. Serum tumor necrosis factor-alpha (TNF-alpha) was measured at baseline and after 3 months of treatment. Transient (TR) or sustained response (SR) was observed in 29 and 16 patients, respectively. Baseline levels of TNF < or = 22 ng/L were observed in 69% of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…More recent comprehensive work at animal models indicates that the synthesis of IL-6 and the activation of STAT3 within hepatocytes are critical functions of Kupffer cells and stimulation of EPO production. [40][41][42][43] Our study is in agreement with that of Lin et al, [44] who followed up 80 chronic HD patients (30 HCVpositive and 50 HCV-negative) in Taipei Medical University Hospital for one year and concluded that lessened anemia was observed in CHC. However, in his study, less erythropoietin was demanded in this group (HCV-positive), whereas our study demonstrated no significant difference of EPO dose between the two groups (HCV-positive and HCV-negative).…”
Section: Discussionsupporting
confidence: 90%
“…More recent comprehensive work at animal models indicates that the synthesis of IL-6 and the activation of STAT3 within hepatocytes are critical functions of Kupffer cells and stimulation of EPO production. [40][41][42][43] Our study is in agreement with that of Lin et al, [44] who followed up 80 chronic HD patients (30 HCVpositive and 50 HCV-negative) in Taipei Medical University Hospital for one year and concluded that lessened anemia was observed in CHC. However, in his study, less erythropoietin was demanded in this group (HCV-positive), whereas our study demonstrated no significant difference of EPO dose between the two groups (HCV-positive and HCV-negative).…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed that the GG genotype of the TNF-α −238 gene promoter is implicated in the probability of liver cirrhosis, supporting our previous data [19] in a different and larger sample of HIV/HCV coinfected patients. Previous data have demonstrated the impact of TNF-α on liver fibrogenesis: increased concentrations of TNF-α have been detected in the liver of patients with chronic hepatitis C [45] and it has been observed that serum levels of this cytokine are correlated with the histological grading score of hepatitis [46]. Likewise, it has been observed that patients with increased serum levels of TNF-α or its receptors showed a reduced survival rate [47].…”
Section: Discussionmentioning
confidence: 98%
“…There are inter-individual variations in detoxifying enzymes and cytokines that could be translated into differences in susceptibility for xenobiotic toxicity and treatment outcomes [13-17]. So in this study, we decided to investigate the association of polymorphisms in the enzymes involved in general oxidative stress defence including NAD(P)H:quinone oxidoreductase-1 (NQO1), Glutathione S-transferases (GST) M1 and T1, and microsomal epoxide hydrolase (EPHX1) enzymes and the two most important cytokines involved in the pathogenesis of liver disease with the basis of inflammation, namely tumor necrosis factor-α (TNF-α) and transforming growth factor-β1 (TGF-β1) cytokines and the treatment outcome of silymarin in the subjects chronically exposed to H 2 S.…”
Section: Introductionmentioning
confidence: 99%